2016
DOI: 10.1038/srep37433
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection of Cultured Human Hepatoma Cells Causes Apoptosis and Pyroptosis in Both Infected and Bystander Cells

Abstract: Individuals infected with hepatitis C virus (HCV) are at high risk of developing progressive liver disease, including cirrhosis and hepatocellular carcinoma (HCC). How HCV infection causes liver destruction has been of significant interest for many years, and apoptosis has been proposed as one operative mechanism. In this study, we employed a tissue culture-adapted strain of HCV (JFH1T) to test effects of HCV infection on induction of programmed cell death (PCD) in Huh-7.5 cells. We found that HCV infection re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 80 publications
(101 reference statements)
2
78
0
Order By: Relevance
“…Uptake of extracellular specks and their escape from endosomes to nucleate further ASC polymerization may be an additional mode of amplifying inflammation that does not rely on other extracellular proteins. The spread of ASC specks between cells could also underlie the transference of pyroptosis to bystander cells co‐cultured with cells infected with HIV and hepatitis C virus . As mentioned above, the mechanisms for the uptake of extracellular ASC specks are unknown, as well as the main cellular types that would mediate their uptake and removal.…”
Section: Physiological Role Of Extracellular Asc Specksmentioning
confidence: 99%
“…Uptake of extracellular specks and their escape from endosomes to nucleate further ASC polymerization may be an additional mode of amplifying inflammation that does not rely on other extracellular proteins. The spread of ASC specks between cells could also underlie the transference of pyroptosis to bystander cells co‐cultured with cells infected with HIV and hepatitis C virus . As mentioned above, the mechanisms for the uptake of extracellular ASC specks are unknown, as well as the main cellular types that would mediate their uptake and removal.…”
Section: Physiological Role Of Extracellular Asc Specksmentioning
confidence: 99%
“…When co-cultured with lymphoid-derived CD4 + T cells, peripheral blood-derived CD4 + T cells become sensitized to HIV-1-induced pyroptosis (140), suggesting that pyroptosis is transmissible between different subsets of cells. Uninfected liver cells can also undergo caspase-1-dependent pyroptosis following infection of bystander cells with hepatitis C virus (HCV) (141). …”
Section: Introductionmentioning
confidence: 99%
“…Due to the significant roles of ROS in the hepatitis pathogenesis [76], it appears that ROS uses inflammasomes to induce the complication as a crucial mechanism. HCV also induces pyroptosis in either infected or bystander liver cells via activation of NLRP3 inflammasome and then caspase-1 [77]. Pyroptosis is an essential main mechanism to induce inflammation, fibrosis and also HCC in the liver.…”
Section: Inflammasomes; the Crucial Inducers Of Chronic Inflammation mentioning
confidence: 99%
“…Sasaki et al, showed that HCV induces cysteine-cysteine chemokine ligand 5 (CCL5) secretion from macrophages, which leads to activation of inflammasomes in the HSCs and subsequently increases the risk of HCC [90]. However, another in vitro investigation presented contrasting results and reported that HCV infection of HCC cell lines is associated with increased apoptosis in the inflammasomes dependent manner [77]. Therefore, it seems that more in vitro and in vivo investigations need to be performed to determine the effects of HBV/ HCV interaction with the inflammasomes on the HCC progression.…”
Section: Inflammasomes; the Crucial Inducers Of Chronic Inflammation mentioning
confidence: 99%
See 1 more Smart Citation